Răspuns :
[tex]a = 2 {x}^{2} + x + 2[/tex]
[tex]b = 2x + 3[/tex]
[tex]a + b = 2 {x}^{2} + x + 2 + 2x + 3 = 2 {x}^{2} + 3x + 5[/tex]
[tex]a - b = 2 {x}^{2} + x + 2 - (2x + 3) = 2 {x}^{2} + x + 2 - 2x - 3 = 2 {x}^{2} - x - 1[/tex]
[tex]a \times b = (2 {x}^{2} + x + 2)(2 x+ 3) = 4 {x}^{3} + 6 {x}^{2} + 2 {x}^{2} + 3x + 4x + 6 = 4 {x}^{3} + 8 {x}^{2} + 7x + 6[/tex]
[tex]b = 2x + 3[/tex]
[tex]a + b = 2 {x}^{2} + x + 2 + 2x + 3 = 2 {x}^{2} + 3x + 5[/tex]
[tex]a - b = 2 {x}^{2} + x + 2 - (2x + 3) = 2 {x}^{2} + x + 2 - 2x - 3 = 2 {x}^{2} - x - 1[/tex]
[tex]a \times b = (2 {x}^{2} + x + 2)(2 x+ 3) = 4 {x}^{3} + 6 {x}^{2} + 2 {x}^{2} + 3x + 4x + 6 = 4 {x}^{3} + 8 {x}^{2} + 7x + 6[/tex]
(2 x² + x + 2)+( 2 x + 3) = 2 x² + 3 x + 5 ⇒ suma
(2 x² + x + 2) - ( 2 x + 3 ) = 2 x² + x + 2 - 2 x - 3 = 2 x² - x - 1 ⇒ diferenta
(2 x² + x + 2)× ( 2 x + 3 ) = 4 x³ + 2 x² + 4 x + 6 x² + 3 x + 6 =
= 4 x³ + 8 x² + 7 x + 6 ⇒ produsul
(2 x² + x + 2) - ( 2 x + 3 ) = 2 x² + x + 2 - 2 x - 3 = 2 x² - x - 1 ⇒ diferenta
(2 x² + x + 2)× ( 2 x + 3 ) = 4 x³ + 2 x² + 4 x + 6 x² + 3 x + 6 =
= 4 x³ + 8 x² + 7 x + 6 ⇒ produsul